2019
DOI: 10.3390/su11226371
|View full text |Cite
|
Sign up to set email alerts
|

Resource Price Fluctuations, Resource Dependence and Sustainable Growth

Abstract: The previous literature on the resource curse has not taken resource price fluctuations into account. Using panel data covering the period from 1993 to 2017 from 28 provinces in China and dynamic generalized method of moments (GMM), this article takes a fresh look at the relationship between resource dependence and sustainable economic growth and the potential transmission mechanisms taking resource price fluctuations into consideration. We find that resource price fluctuations represent an important factor wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The brain drain in high-tech industries eventually leads to the overdevelopment of resource-based industries. As a result, other industries have no impetus for development and are squeezed [12,13].…”
Section: Literature Review and Theoretical Mechanism 21 Resource Endo...mentioning
confidence: 99%
“…The brain drain in high-tech industries eventually leads to the overdevelopment of resource-based industries. As a result, other industries have no impetus for development and are squeezed [12,13].…”
Section: Literature Review and Theoretical Mechanism 21 Resource Endo...mentioning
confidence: 99%
“…(2) Resource dependence is an essential indicator to measure the regional economic structure and income structure, reflecting the importance of resource development to economic development and the dependence of herders' livelihoods on natural resources. There is an inverted U-shaped relationship between resource dependence and economic growth, when resource dependence is lower than a certain critical value, the improvement of resource dependence can promote economic growth [33]. Due to the inevitable conflict between resource protection and community economic development in national parks [34], the degree of dependence of local herders' livelihoods on resources is directly related to the coordination level between ecological protection of national parks and income increase of herders.…”
Section: Research Hypothesismentioning
confidence: 99%
“…These studies analyzed the existence of the resource curse under different research scales and put forward the optimal path and policy suggestions for resource-based economic transformation. Simultaneously, a few studies have analyzed the transmission mechanism of the "resource curse" effect from many aspects, such as material capital input, human capital input, and technological innovation input [42][43][44][45]. Most studies in China have concluded a resource curse, especially in the country's fast-growing central and western regions, but some have found a different story [46].…”
Section: Literature Reviewmentioning
confidence: 99%